miR-135b Stimulates Osteosarcoma Recurrence and Lung Metastasis via Notch and Wnt/β-Catenin Signaling - Hua Jin; Song Luo; Yun Wang; Chang Liu; Zhenghao Piao; Meng Xu; Wei Guan; Qing Li; Hua Zou; Qun-You Tan; Zhen-Zhou Yang; Yan Wang; et al. (Elsevier, 2017)
Cancer stem cells (CSCs) play an important role in osteosarcoma (OS) metastasis and recurrence, and both Wnt/β-catenin and Notch signaling are essential for the development of the biological traits of CSCs. However, the mechanism that underlies the simultaneous hyperactivation of both Wnt/β-catenin and Notch signaling in OS remains unclear. Here, we report that expression of miR-135b correlates with the overall and recurrence-free survival of OS patients, and that miR-135b has an activating effect on both Wnt/β-catenin and Notch signaling. The overexpression of miR-135b simultaneously targets multiple negative regulators of the Wnt/β-catenin and Notch signaling pathways, including glycogen synthase kinase-3 beta (GSK3β), casein kinase 1a (CK1α), and ten-eleven translocation 3 (TET3). Therefore, upregulated miR-135b promotes CSC traits, lung metastasis, and tumor recurrence in OS. Notably, antagonizing miR-135b potently inhibits OS lung metastasis, cancer cell stemness, CSC-induced tumor formation, and recurrence in xenograft animal models. These findings suggest that miR-135b mediates the constitutive activation of Wnt/β-catenin and Notch signaling, and that the inhibition of miR-135b is a novel strategy to inhibit tumor metastasis and prevent CSC-induced recurrence in OS. Keywords: osteosarcoma, miR-135b, metastasis, recurrence, Wnt/β-catenin